Occlusal adjustment in dental prosthesis: a literature review (Research, Society and Development, 2022)
Dental prostheses are responsible for reestablishing the absence of dental elements. Occlusal adjustment is a crucial step within the oral rehabilitation treatment, where the occlusal surface modification occurs through selective wear or addition of material. Occlusal adjustment should be understood by the professionals since there is evidence of negative effects in the absence of an adequate and balanced occlusal scheme. The objective of this study was to develop a literature review about occlusal principles according to the prosthesis and concepts of occlusion necessary for a good oral rehabilitation. The mandibular movements are guided by the teeth, and the prosthesis should mimic the dental morphology and restore the lost function through disocclusion guidance and correct distribution of dental contacts. Scientific evidence should orient the best adjustment for each type of prosthesis. It is the responsibility of the dental surgeon to diagnose the absence of occlusal harmony and, through the prosthetic work, bring back the occlusal balance and the masticatory system health.